Between Sexual Violence and Autonomy: Rethinking the Engagement of the Indian Women's Movement with Criminal Law. Issue 5 (August 2021) - Mehta, Kalika; Tiwari, Avantika
Abstract: The aftermath of protests triggered by a brutal gang-rape in New Delhi in December 2012 was archetypal of the broader women's movement in post-independence India. The primary demands of the social movement to address sexual violence against women were wrapped in the language of rights-based reforms in criminal law provisions. The state responded to the social mobilization in the form of criminal law amendments, while blindsiding key recommendations from feminist groups. This Article revisits pertinent Law Commission reports, subsequent criminal law reforms, and case law on sexual violence against women to analyze how the negotiations between the women's movement and the State on the seemingly irreconcilable demands of sexual autonomy and punishment for sexual violence. We take account of the intended and unintended consequences of this reliance on criminal law as one of the primary tools in the arsenal of Indian women's movements. We argue that engagement on the plane of criminal law to address sexual violence against women is a case of limited imagination at best and counter-productive at its worst. This approach of the movement and feminist groups is to react to the "crime" of sexual violence after the fact, leading to distraction from much warranted structural responses. We argue that this approach makes it harder to conceptualize and implement more forward-looking relational models of responsibility that are necessary to address the structural injustice of systemic sexual violence against women.